PELATIHAN DAN PENDAMPINGAN PENGELOLAAN SAMPAH ORGANIK MENJADI PUPUK ORGANIK DAN ECO ENZYM UNTUK TERCIPTANYA LINGKUNGAN BERSIH, SEHAT DAN BERKELANJUTAN - I Wayan Suanda; Kadek Intan Rusmayanthi; I Gusti Ayu Rai; I Made Subrata (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
Environmental cleanliness starting from the household environment, school, footpath and the wider environment really needs to be maintained together from garbage. SMP Negeri 11 Denpasar is located on the edge of Serangan Island beach and really needs shade trees, a fairly large playground and sports yard, lots of shade trees and the school canteen is a source of organic waste that needs to be managed properly. The existence of garbage really disturbs the beauty, beauty and source of disease and other negative impacts, so it needs to be managed properly so that there is no pile of garbage and reduces the sending of garbage to TPS. Management of organic waste into organic fertilizer and eco enzyme is a form of innovation and creativity to maintain the cleanliness of the school environment. Innovation and creativity can be implemented through community service activities in the form of training and mentoring in managing waste into organic fertilizer and eco enzyme. Community service activities can be carried out in collaboration with academics from universities as a form of implementing Tridharma. Training and mentoring in managing waste into organic fertilizer and eco enzyme is carried out in the school yard, so there will be interaction between students and the natural environment as a form of deep learning. The implementation of community service can be packaged in such a way that students can carry out activities well and happily as a form of developing the knowledge gained in classroom learning.